Prospects for Adding Drugs with Known Anti-tuberculosis Activity to the Composition of Bone Cement for Treatment of Tuberculous Arthritis - E. O. Peretsmanas; V. S. Zubikov; A. E. Panova; A. N. Gracheva; A. A. Kazyulina; I. A. Gerasimov (Туберкулез и болезни лёгких)
The objective: to evaluate the possibility of using linezolid, amikacin, levofloxacin and bedaquiline mixed with bone cement for the treatment of patients with tuberculous arthritis taking into account changes in mechanical properties of bone cement, antimycobacterial activity of drugs and characteristics of their release.Subjects and Methods. The antimycobacterial, elution and strength characteristics of bone cement mixed with the drugs known for their anti-tuberculosis activity were studied: linezolid, amikacin, levofloxacin, and bedaquiline. The antimycobacterial effect was evaluated by the minimum inhibitory concentration (MIC) of the reference strain of Mycobacterium tuberculosis H37RV sensitive to anti-tuberculosis drugs (TB drugs). To study the kinetics of elution, the methods of high-performance mass spectrometry and spectrophotometry were used. The strength characteristics were determined using LFM-50 electromechanical testing machine.Results. The obtained results demonstrated satisfactory elution and antimycobacterial parameters for linezolid and amikacin, thus they can be mixed with bone cement, and the cement retained its strength characteristics. Levofloxacin showed antimycobacterial activity only within 1 day after the cement sample was immersed in the solution. Bedaquiline showed negative elution and antimycobacterial characteristics in the cement sample.